Análise do discurso poético mítico da personagem Iracema de José de Alencar - Silva, Flávia da (2009)
This dissertation proposes to analyze the degrees of poeticity constant in the construction of the myth of Iracema in the homonymous novel of 1865, taking into account its relation with the language, the memory/imagination dialogue and the figurative creation of the character s image. The analytic path was built parting from the specific universe of book covers and xylographs, considering the romantic period s vision, when the novel Iracema by Jose de Alencar, was written and published. Monuments, built in tribute to the legendary character and its place of origin: Ceara, were also presented and analysed. Hence, we looked for support in some concepts that address the mythological character of our protagonist, to then, immediately establish links with Iracema-the myth, the theme-character of this study. To do this, her qualities as a sacralized figure depicted in a painting will be referred to, in order to give evidence to certain potentials; the glorification of the nationality, the terra mater archetype, the founding myth. Alencar deliberately projected this novel to reveal its civilizational proposition: representation of romantic nationalism; insertion of memory/imagination dialogue; author-reader interaction. Having this in mind, he analyzed and described the character Iracema within an amorous, idyllic prism, parting from its etymologic root (the name ira meaning lips of honey in the Tupi language, or reverberation of America) all the way to possible deductions with the New World matrix Moacir s mother son of the wild one invaded by the colonizer, represented by the white man Martin. Moacir, half-breed son, survivor and first element of a new race. A game of tension between the lyric subject and the humanized Eros, this legend, now a fiction, is woven around a single character, a paper woman , the image of fertility, that represents the interior, that is, the mountains, (therefore, land) in a dialogue with Martin, a warrior from another space the sea he that comes and goes, a traveler that does not fix himself anywhere. Also a game of tension between Eros and Thanatos, this narrative portrays an Iracema who dies to give life, who dies to become a myth. She represents the land America for which she suffered condemnation; the son represents the result of this movement of transformation, to be more exact, miscigenation. The work, in our view, problematizes the reading that is a poetic founder myth of a new literary and poetic discourse, innovative in the sphere of the brazilian XIXth century novel